Sliding Mode Control of the Haptic-Teleoperation System Based on a Real and Virtual Robot - Abut, Tayfun; Soyguder, Servet (Ieee, 2019)
The purpose of this paper to realize bilateral control of the haptic-teleoperation system consisting of a real and virtual robot. The equations of motion of the robots that make up the system are obtained. The system is modeled based on the structural similarity between the real Phantom Omni master robot and the virtual slave Phantom Omni Robot. A visual interface is designed in a virtual environment to visualize the movements of the slave robot. Bilateral control of the system was carried through by using the Sliding Mode Control (SMC) and classical PID control methods. PID control methods. The results are given by graphs and examined.
International Conference on Artificial Intelligence and Data Processing (IDAP) -- SEP 21-22, 2019 -- Inonu Univ, Malatya, TURKEY
Keywords: Haptic-Teleoperation; Phantom Omni; Virtual Reality; Human-Robot Interaction (HRI)